ypN0 nodal status after neoadjuvant chemoradiotherapy for rectal carcinoma is not associated with adverse prognosis as compared with pN0 after primary surgery - Erlenbach-Wuensch, Katharina; Semrau, Sabine; Fietkau, Rainer; Weber, Klaus; Hohenberger, Werner; Rau, Tilman; Hartmann, Arndt; Merkel, Susanne; Agaimy, Abbas (International Journal of Colorectal Disease, 2014)
Neoadjuvant chemoradiotherapy (nCRT) has been established as standard treatment for locally advanced rectal cancer (cT3/4 or cN+ cM0, distance from circumferential resection margin <=1 mm) to enhance local disease control and minimize the rate of locoregional recurrence. As a consequence of downstaging, a significant proportion of patients show non-viable tumor deposits within regional lymph nodes that qualify as ypN0 according to the current TNM classification irrespective of the actual pre-treatment status. Accordingly, the prognostic relevance of ypN0 status as compared with true pN0 without preceding nCRT is not known.We retrospectively analyzed 132 patients who underwent standard total mesorectal excision (TME) surgery after nCRT for rectal carcinoma and were classified as ypN0, and compared their prognoses with those of 341 patients with pN0 without nCRT.Re-evaluation of regional lymph nodes after nCRT showed no evidence of previous metastasis in 91 cases (ypN0(-)), sure but non-viable metastasis in 14 patients (ypN0(+)), and unsure status in 27 patients (ypN0(X)). The local recurrence rate, distant metastases, and disease-free, observed, and cancer-related survival were similar in all subgroups (p = 0.447, 0.695, 0.759, 0.655, and 0.354, respectively).Our results showed a similar outcome in patients with ypN0 and in the control group with pN0 regarding local recurrence rate, distant metastases, and disease-free, observed, and cancer-related survival. Validation of these results is necessary to clarify the questions regarding postoperative adjuvant chemotherapy for patients with ypN0(+).
EVALuna2:6516